Expert workshop on NAMAs: National mitigation planning and implementation in agriculture - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2012)
The purpose of the workshop was to support the development of national mitigation planning to advance climate smart agriculture. Key messages resulting from the workshop: